(untitled) (Comprehensive Journal of Science, 2025)
The research provides a comprehensive study of the aesthetic and architectural values manifested in the domes used in the Prophet’s Mosque throughout its various historical stages. It focuses on the artistic, symbolic, functional, and technological elements in dome design. The research also examines the evolution of the domes from the early Islamic periods to the modern Saudi expansions, in addition to reviewing the geometric methods, environmental treatments, and formal significances in Islamic architecture. The research aims to present an integrated academic analytical study that can be relied upon in postgraduate studies. The study reached some of the following results: the domes of the Prophet’s Mosque evolved from simple domes to advanced technologies such as movable domes in the modern era. The decorations are an integral part of the structural and geometric design of the dome; they are drawn and executed in harmony with the concave geometric shape of the ceiling, creating an integration between structural function and aesthetic value. The technique of mosaics made from small pieces of pure gold and colored glass mosaics was employed, showcasing high craftsmanship in cutting and assembly. The windows designed at the base of the dome interact with the golden and colored surfaces, reflecting sunlight in a way that enhances the brilliance of the colors and creates changing light effects throughout the day, adding a dynamic dimension to the static decoration.